EVALUASI DAN PENGEMBANGAN ALTERNATIF DESAIN ANTARMUKA E-CAMPUS STIKOM AMBON - Amran Suatkab; Harry B. Santoso (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2018)
E-Campus is a support media of administration and academic activities system that used to improve the effectiveness and efficiency of campus activities. However, e-Campus is created and developed by the public to meet the needs in general, which means it is not created to the specific needs of the campus that impact on campus administration and academic activities such as unused features or those that unrelated to campus activities. Furthermore, for students and lecturers, there are parts of the form that are not complete, and so forth. Evaluation with e-Campus system is done by multi method which consist of usability test, that is observing respondent difficulties in utilizing function / e-Campus feature specifically, and system usability scale to assess system as a whole. The results show that none of the scenarios were successfully resolved without help (hint). The completion rate for tasks 13 and 18 is 0% of all users and furthermore, not all tasks were completed on time. The main problem lies in the page view, toolbar, navigation system and incomplete pages. The e-campus prototype was built based on Shneiderman’s 8 Golden Rules of Interface Design with considerations on inputs from the evaluation process